Use of steel slags in automobile road construction - Krayushkina, Kateryna; Prentkovskis, Olegas; Bieliatynskyi, Andrii; Junevičius, Raimundas (Transport, 2012)
Building and, especially, reconstruction and repairs of highways, call for the development of stone materials manufacturing industry. Increasing need for stone materials may be satisfied by a wide use of industrial waste and secondary resources. In road building, slag of ferrous and nonferrous metallurgy is one of the most popular wastes which are increasingly widespread with every year. Such slag is a valuable raw material for preparation of macadam materials and mineral binders serving as a base for asphalt concrete mixtures and manufacturing of cement emulsions, which are widely used in road paving. The research focused on the use of different types of slag in road construction in Ukraine. Possibilities of using crushed rock and sand as recrement slag of different production for preparation of asphalt concrete and cement mixtures to be used for road-base was studied, as well as the use of slag materials for construction of lower category roads. In the given work, the opportunity to recycle electric furnace steel-smelting slag for preparation of asphalt concrete mixtures was defined.First Published Online: 26 Jun 2012